The Influence of Good Corporate Governance on Firm Value with Financial Performance as a Moderation - Andrinaldo, Arisky; Kesuma, Indrawati Mara; Alfarizi, Randi (Journal of Accounting Auditing and Business, 2024)
This study investigates the direct and moderating effects of various corporate governance factors on firm value. The direct effect analysis reveals that financial performance alone does not significantly influence firm value, whereas the roles of independent commissioners and independent directors are crucial, significantly enhancing firm value through improved governance and oversight capabilities. Conversely, the direct impact of independent audits on firm value is found to be non-significant, suggesting their influence is more indirect, supporting a trustworthy financial environment. The moderating effect analysis underscores the importance of corporate governance in leveraging financial performance to enhance firm value. Independent commissioners, directors, and audits all have significant moderating effects, enhancing the positive relationship between financial performance and firm value. Independent commissioners and directors ensure effective utilization of financial gains and risk mitigation, while independent audits ensure the reliability and transparency of financial reporting, building investor trust and confidence. Combining insights from both analyses, the study concludes that effective corporate governance is paramount in maximizing firm value. Strong governance structures, including the inclusion of independent commissioners, directors, and auditors, not only directly enhance firm value but also amplify the positive effects of financial performance. This study emphasizes the need for stakeholders and policymakers to prioritize strengthening corporate governance frameworks to achieve sustainable value creation.